CALCULATION OF CENTRAL MOMENTS OF DIFFERENTIAL MELTING CURVE OF DNA MOLECULE - Ghazaryan, R.S.; Hakobyan, S.N.; Shahinyan, M.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2020)
Central moments of function of the differential melting curve (DMC) of DNA have been calculated through expansion of block DNA DMC to Gaussian components. Calculations showed that the first moment of DNA DMC characterizes the melting temperature, the second is DNA melting interval. Central moments of the third and fourth orders characterize distribution of nucleotides along DNA chain. It was shown that the distribution of nucleotides along DNA chain differs from quasi-arbitrary distribution.
Keywords: differential melting curve, central moments of DMC of DNA